S7A:6 Baseline serum levels of baff or april are independent predictors of sledai response after 12 months of treatment with belimumab in patients with refractory systemic lupus erythematosus. (21st March 2018) - Piantoni, S; Andreoli, L; Lowin, T; Kumar, R; Regola, F; Airò, P; Franceschini, F; Tincani, A; Pongratz, G
Abstract : Background: Belimumab, a monoclonal antibody targeting BlyS (B lymphocyte stimulator), is used in refractory Systemic Lupus Erythematosus (SLE). Pivotal clinical trials showed that SLE patients with positive anti-dsDNA antibodies and reduced levels of C3 and/or C4 fractions were those more likely to be responders to treatment. Our study aims at exploring predictors of response to Belimumab in the post-marketing experience in consecutive SLE patients treated at a single centre. Methods: Twenty-one patients received Belimumab intravenously at standard regimen (10 mg/kg at 0–15–30 days and then every 4 weeks). Anti-dsDNA were tested by Farr assay and C3/C4 levels by nephelometry. Biomarkers belonging to the TNF superfamily and related to B cell activity (BAFF, APRIL, sBCMA, sCD40L, sTACI, TWEAK) were tested by ELISA. All laboratory parameters were tested at baseline and every 6 months afterwards. SLE disease activity was assessed by SLEDAI-2K score. General linear modelling and correlation analysis were performed using SPSS. Results: Enrolled patients were 2 males and 19 females with a median (25th-75th percentile) age of 38 (31–42) years. The disease duration at time of Belimumab start was 12 (8–19) years. The baseline SLEDAI score was 6 (4–9), the anti-dsDNA level was 26 (11–99) UI/ml, and their C3 and C4 level was 72 (56–86) and 9 (7–15) mg/dL, respectively. All the parameters of the TNF superfamily showed moderate/strong correlation (r values ranging from 0.543 and 0.989, p<0.01). With and without correction for different variables, BAFF and APRIL serum levels measured at the start of Belimumab treatment were the most robust predictors of relative SLEDAI reduction after 12 months of treatment (table 1). In contrast, C3, C4, anti-dsDNA, and SLEDAI were less likely to predict relative SLEDAI change at 12 month of Belimumab treatment (uncontrolled model: C3 p=0.410; C4 p=0.778; anti-dsDNA p=0.412) in this cohort of patients preselected for the treatment with Belimumab. Conclusions: In this preselected 'real-life' cohort of refractory SLE patients fulfilling the requirements for Belimumab treatment baseline serum levels of BAFF or APRIL are independent predictors of response to treatment. Therefore, BAFF and APRIL could be useful for response estimation in patients qualifying for Belimumab treatment.